Integrating phytoplankton functional groups and water quality indices to assess tropical swamp forest ecology - Gani, Md Ataul; Islam, Shahima; Shafi, Shafiul Azom; Hasan, Md Mehedi; Alfasane, Md Almujaddade (Bangladesh Journal of Plant Taxonomy, 2025)
Tropical swamp forests are dynamic ecosystems where water quality is closely linked to ecological integrity. The Ratargul Swamp Forest in Bangladesh faces increasing anthropogenic and environmental pressures, but a comprehensive ecological assessment integrating biological and physicochemical indicators is lacking. The present study was conducted to evaluate its ecological status, identify key environmental drivers, and assess the utility of financial groups (FGs) as bioindicators for conservation. In the present study, the ecological condition of the forest was assessed by integrating phytoplankton FGs with the water quality index (WQI) and the chlorophyll-based trophic state index [TSI (Chl)] during the pre-monsoon and post-monsoon seasons. A total of 54 phytoplankton species were identified from the swamp forest, with Euglenophyta dominating the assemblage. Functional group W1 (Euglena sp., Euglena mutabilis, E. rostrifera, E. viridis, E. oblonga, E.acus, E. polymorpha, E. chordata, E. allorgei, E. deses, Phacus sp., Phacus longicaudus. Strombomonas sp., Synura sp. and Astasia sp.) associated with organic pollution and high biological oxygen demand (BOD), were the most abundant in both seasons, with a marked increase post-monsoon. Redundancy analysis (RDA) revealed that soluble reactive phosphorus (SRP), soluble reactive silicate (SRS), and conductivity were the key environmental drivers influencing the composition of FGs. The water quality of the swamp forest was poor, as indicated by the WQI, which was based on the selection of water quality parameters (R² = 0.85). The TSI (Chl) supported the WQI result, indicating the eutrophic status of the forest. The present research findings showed that phytoplankton functional groups, when integrated with water quality indices, offer a robust and sensitive approach to ecological monitoring and planning conservation strategies for tropical swamp forest wetland ecology. Bangladesh J. Plant Taxon. 32(2): 193-207, 2025 (December)